Ahamm al-Muṣṭalaḥāt al-Ḥadīthiyyah al-Muʻtabarah ʻInd al-Muḥaddithīn - Sahabuddin Sahabuddin (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2007)
This paper relates with the science of hadith that explains the terms in books of hadith such as Musnad, Sunan, Muwatta, shahifah, jami ', musannaf etc; and the terms used in their books include authentic, hasan, dha'if, Gharib, mutawatir, ahad, muttafaq 'alaih etc. This exposure is important to the reader understand the terms used by scholars of hadith in their books.